Invariant Einstein metrics on generalized flag manifolds of $Sp(n)$ and $SO(2n)$ - Luciana Aparecida Alves; Neiton Pereira da Silva (Boletim da Sociedade Paranaense de Matemática, 2018)
It is well known that the Einstein equation on a Riemannian flag manifold $(G/K,g)$ reduces to an algebraic system if $g$ is a $G$-invariant metric. In this paper we obtain explicitly new invariant Einstein metrics on generalized flag manifolds of $Sp(n)$ and $SO(2n)$; and we compute the Einstein system for generalized flag manifolds of type $Sp(n)$. We also consider the isometric problem for these Einstein metrics.